Suicide Within 72 Hours After Discharge From Health Care Settings: Decedent Characteristics. (March 2016) - Drake, Stacy A.; Garza, Brenda; Cron, Stanley G.; Wolf, Dwayne A.
Abstract : Abstract: Health care providers have the challenge of identifying patients at risk of committing suicide after discharge from their care. The aim of this study was to identify and describe the population committing suicide less than 72 hours after discharge from medical care. Between 2006 and 2014 in Harris County, Texas, 30 individuals were identified who met these criteria. The decedents included 27 men and 3 women with a mean age of 43.5 years. The cause of death in most cases was gunshot wound of the head. Five of the decedents had requested discharge or left against medical advice and 24 committed suicide within 24 hours. Although the sample size is small, it is one of the largest cohorts of its type.